Attenuated Cytokine-Induced Memory-Like Natural Killer Cell Responses to Mycobacterium tuberculosis in Tuberculosis Patients - Liang C; Li S; Yuan J; Song Y; Ren W; Wang W; Shang Y; Tang S; Pang Y (Infection and Drug Resistance, 2023)
Chen Liang,1,2,* Shanshan Li,1,* Jinfeng Yuan,1 Yanhua Song,3 Weicong Ren,1 Wei Wang,1 Yuanyuan Shang,1 Shenjie Tang,2 Yu Pang1 1Department of Bacteriology and Immunology, Beijing Key Laboratory on Drug-Resistant Tuberculosis Research, Beijing Chest Hospital, Capital Medical University /Beijing Tuberculosis and Thoracic Tumor Research Institute, Beijing, 101149, People’s Republic of China; 2Tuberculosis Clinical Medical Center, Beijing Chest Hospital, Capital Medical University /Beijing Tuberculosis and Thoracic Tumor Research Institute, Beijing, 101149, People’s Republic of China; 3Department of Tuberculosis, Beijing Chest Hospital, Capital Medical University/Beijing Tuberculosis and Thoracic Tumor Research Institute, Beijing, 101149, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shenjie Tang; Yu Pang, Beijing Chest Hospital, Capital Medical University, No. 97, Machang, Tongzhou District, Beijing, 101149, People’s Republic of China, Tel/Fax +86 010 8950 9367 ; +86 010 8950 9359, Email tangsj1106@vip.sina.com; pangyupound@163.comPurpose: This study aimed to investigate the phenotype, proliferation and functional alterations of cytokine-induced memory-like natural killer (CIML NK) cells from healthy subjects and TB patients, and assessed the efficacy of CIML NK cells in response to H37Rv-infected U937 cells in vitro.Methods: Fresh peripheral blood mononuclear cells (PBMCs) were isolated from healthy people and tuberculosis patients and activated for 16h using low-dose IL-15, or IL-12, IL-15, IL-18 combination or IL-12, IL-15, IL-18 and MTB H37Rv lysates, respectively, followed by low-dose IL-15 maintenance for another 7 days. Then, the PBMCs were co-cultured with K562 and H37Rv-infected U937, and the purified NK cells were co-cultured with H37Rv infected U937. The phenotype, proliferation and response function of CIML NK cells were assessed using flow cytometry. Finally, colony forming units were enumerated to confirm the survival of intracellular MTB.Results: CIML NK phenotypes from TB patients were similar to healthy controls. CIML NK cells undergo higher rates of proliferation after IL-12/15/18 pre-activation. Moreover, the poor expansion potential of CIML NK cells co-stimulated with MTB lysates. CIML NK cells from healthy individuals showed enhanced IFN-γ functional to H37Rv infected U937 cells, along with significantly enhanced killing of H37Rv. However, the CIML NK cells from TB patients show attenuated IFN-γ production and now enhanced the ability of killing intracellular MTB compared to those from healthy donors after co-cultured with H37Rv infected U937.Conclusion: CIML NK cells from healthy individuals exist the increased ability of IFN-γ secretion and boosted anti-MTB activity in vitro, which from TB patients show impaired IFN-γ production and no enhanced anti-MTB activity compared to those from healthy donors. Additionally, we observe the poor expansion potential of CIML NK cells co-stimulated with antigens from MTB. These results open up new possibilities for NK cell-based anti-tuberculosis immunotherapeutic strategies.Keywords: Mycobacterium tuberculosis, cytokines, NK cells, memory-like NK cells, IFN-&#x03B3